2021
DOI: 10.1111/cge.13979
|View full text |Cite
|
Sign up to set email alerts
|

PPP3CA truncating variants clustered in the regulatory domain cause early‐onset refractory epilepsy

Abstract: PPP3CA encodes the catalytic subunit of calcineurin, a calcium‐calmodulin‐regulated serine–threonine phosphatase. Loss‐of‐function (LoF) variants in the catalytic domain have been associated with epilepsy, while gain‐of‐function (GoF) variants in the auto‐inhibitory domain cause multiple congenital abnormalities. We herein report five new patients with de novo PPP3CA variants. Interestingly, the two frameshift variants in this study and the six truncating variants reported previously are all located within a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Protein Phosphatase 3 Catalytic Subunit Alpha ( PPP3CA, Log 2 FC = − 0.72; p.adj = 0.026) enables several functions, including ATPase binding activity, CaM binding activity, and CaM -dependent protein phosphatase activity, calcineurin-NFAT signaling cascade, peptidyl–serine dephosphorylation and response to Ca 2+ ion. RCAN3 (Log 2 FC = 0.73; p.adj = 0.004) encodes for RCAN Family Member 3 and is involved in Ca 2+ -mediated signaling, inhibiting calcineurin-dependent transcriptional responses by binding to the catalytic domain of calcineurin A [ 72 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Protein Phosphatase 3 Catalytic Subunit Alpha ( PPP3CA, Log 2 FC = − 0.72; p.adj = 0.026) enables several functions, including ATPase binding activity, CaM binding activity, and CaM -dependent protein phosphatase activity, calcineurin-NFAT signaling cascade, peptidyl–serine dephosphorylation and response to Ca 2+ ion. RCAN3 (Log 2 FC = 0.73; p.adj = 0.004) encodes for RCAN Family Member 3 and is involved in Ca 2+ -mediated signaling, inhibiting calcineurin-dependent transcriptional responses by binding to the catalytic domain of calcineurin A [ 72 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2008, Wang et al reported that PPP3CA modulates the VEGF-stimulated cell proliferation and signaling cascades in cells ( 47 ). PPP3CA is a serine/threonine phosphatase regulated by Ca 2+ /CaM ( 48 , 49 ). Gelernter et al found that PPP3CA encodes a calcium-dependent, calmodulin-stimulated protein phosphatase involved in calcium signaling ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function pathogenic variants cause autosomal dominant developmental and epileptic encephalopathy 91 (OMIM#617,711). This disorder is characterized by early-onset epilepsy (severity is variable and may be correlated with the specific variant), moderate/severe DD/ID, developmental regression, autistic behavior, generalized muscular hypotonia or spasticity, talipes equinovarus, feeding difficulties, cortical vision loss, cerebral atrophy and delayed myelinization [ 28 30 ]. Gain-of-function pathogenic variants lead to a syndrome characterized by arthrogryposis, cleft palate, craniosynostosis and ID (OMIM#618,265).…”
Section: Discussionmentioning
confidence: 99%